Incident cancers attributable to using opium and smoking cigarettes in the Golestan cohort studyResearch in context - Karine Alcala; Hossein Poustchi; Vivian Viallon; Farhad Islami; Akram Pourshams; Alireza Sadjadi; Saeed Nemati; Masoud Khoshnia; Abdolsamad Gharavi; Gholamreza Roshandel; Maryam Hashemian; Sanford M. Dawsey; et al. (EClinicalMedicine, 2023)
Summary: Background: Opium consumption has recently been identified as a carcinogen, but the impact of opium use on cancer burden is unknown. We aimed to evaluate the fraction of cancers that could be attributed to opium use alone and in combination with cigarette smoking in a region where opium is widely used. Methods: 50,045 Iranian adults were recruited to this prospective cohort study between 2004 and 2008 and were followed through January 2022. We assessed the association between using opium and/or cigarette smoking and various cancers using proportional hazards regression models. We then calculated population attributable fractions (PAFs) for all cancers and for groups of cancers causally linked to opium and cigarette smoking. Findings: Of the total participants, 8% only used opium, 8.3% only smoked cigarettes, and 9% used both substances. During a median 14 years of follow-up, 2195 individuals were diagnosed with cancer, including 215 opium-related cancers (lung, larynx, and bladder) and 1609 tobacco-related cancers (20 types). Opium use alone was estimated to cause 35% (95% CI: 26%–45%) of opium-related cancers, while smoking cigarettes alone was estimated to cause 9% (6%–12%) of tobacco-related cancers in this population. Using opium and/or cigarettes was estimated to cause 13% (9%–16%) of all cancers, 58% (49%–66%) of opium-related cancers, and 15% (11%–18%) of tobacco-related cancers. Moreover, joint exposure to opium and cigarettes had the greatest impact on cancers of the larynx, pharynx, lung, and bladder, with PAFs ranging from 50% to 77%. Interpretation: Using opium and smoking cigarettes account for a large proportion of cancers in this population. To reduce the cancer burden, prevention policies should aim to decrease the use of both substances through public awareness campaigns and interventional efforts. Funding: The Golestan Cohort Study work was funded by the Tehran University of Medical Sciences, Cancer Research UK, U.S. National Cancer Institute, International Agency for Research on Cancer. The presented analysis was supported by the International HundredK+ Cohorts Consortium (IHCC).